The origin of human CD20+ T cells: a stolen identity? - von Essen, Marina Rode; Stolpe, Lisbeth Egelykke; Bach Søndergaard, Helle; Sellebjerg, Finn (Frontiers in Immunology, 2024)
Human T cells expressing CD20 play an important role in the defense against virus and cancer and are central in the pathogenesis of both malignancies and various autoimmune disorders. Therapeutic modulation of CD20+ T cells and the CD20 expression level is therefore of significant interest. In rodents, CD20 on T cells is likely the product of an active transfer of CD20 from a donor B cell interacting with a recipient T cell in a process termed trogocytosis. Whether the same applies to human CD20+ T cells is highly debated. Investigating this dispute showed that human CD20− T cells could achieve CD20 along with a series of other B-cell markers from B cells through trogocytosis. However, none of these B-cell markers were co-expressed with CD20 on human CD20+ T cells in blood or inflamed CSF, implying that additional mechanisms may be involved in the development of human CD20+ T cells. In support of this, we identified true naïve CD20+ T cells, measured endogenous production of CD20, and observed that CD20 could be inherited to daughter cells, contradicting that all human CD20+ T cells are a product of trogocytosis.